SLC7 transporters at the crossroads of amino acid metabolism and diabetes pathophysiology: insights and therapeutic perspectives - Xu, Tingting; Zhang, Xiaoshi; Chen, Qingqing; Yang, Cheng; Deng, Bo; Armstrong, David G.; Rui, Shunli; Zhou, Yueqin; Deng, Wuquan (Frontiers in Nutrition, 2025)
Amino acids are fundamental components of all living cells, serving not only as the building blocks of proteins but also as crucial sources of energy and precursors to key metabolites and signaling molecules. Amino acid transporters, specialized membrane proteins, facilitate the movement of amino acids across plasma membranes and between various cells and organ compartments. The malfunction, absence, or overexpression of specific amino acid transporters is linked to several human diseases. Among the extensive family of solute carrier proteins (SLCs), which comprises 458 transporters, the SLC7 transporter family, inclusive of CATs (Cationic Amino Acid Transporters) and LATs (L-type Amino Acid Transporters), is particularly instrumental in cellular amino acid uptake. Disruptions in amino acid transport can lead to significant metabolic abnormalities in diabetes, characterized by impaired insulin signaling and altered glucose metabolism. A deeper understanding of amino acid transporters’ roles in metabolic processes and insulin signaling could shed light on the pathogenesis of diabetes and unveil novel therapeutic targets for this pervasive metabolic syndrome.